CALAGEM SUPERFICIAL, UMIDADE DO SOLO E COMPORTAMENTO DO MILHO CULTIVADO EM SISTEMA PLANTIO DIRETO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
The effects of soil acidity in a no-till system need to be further investigated under drought. The corn performance in response to surface application of lime, as affected by aluminum genotypic tolerance and soil moisture was evaluated in a sandy clay loam Typic Hapludox, in Ponta Grossa, Parana State, Brazil. The study was carried out in a field experiment and in undisturbed soil columns. In a field experiment, the changes in soil chemical attributes at 0-5, 5-10, 10-20, 20-40 and 40-60 cm depths, and the nutrition, export and nutrient uptake, above ground biomass and grain yield of corn in 2008-2009 were evaluated after surface application of lime at rates of 0, 4, 8 and 12 t ha-1 in 2004, in a randomized complete block with three replications. Undisturbed soil columns were removed from plots that received lime rates, and another experiment was carried out on them, testing two hybrids, one aluminum-sensitive and another moderately sensitive to aluminum, and two moisture levels, simulating the presence and absence of water stress. Surface liming ameliorated soil acidity in all depths studied, and improved root environment throughout profile. Corn root growth was influenced by lime application, mainly at 0-10 cm depth. Liming had a positive effect on nutrition, export and nutrient uptake, resulting in a significant increase in corn grain yield. In the undisturbed columns, soil amendment by surface liming benefited root growth, nutrient uptake and dry matter production of corn plants, mainly in a water stress condition. In general, there was no difference in the response of both sensitive hybrid and moderately sensitive hybrid to aluminum toxicity with liming. It is concluded that the corn crop performance is ameliorated by the reduction in soil acidity through surface liming under no-till, but the corn crop development is little influenced by soil acidity when water availability is adequate. However, in a water stress condition, the soil acidity severely compromises the corn crop development under no-till system. The effects of soil acidity in a no-till system need to be further investigated under drought. The corn performance in response to surface application of lime, as affected by aluminum genotypic tolerance and soil moisture was evaluated in a sandy clay loam Typic Hapludox, in Ponta Grossa, Parana State, Brazil. The study was carried out in a field experiment and in undisturbed soil columns. In a field experiment, the changes in soil chemical attributes at 0-5, 5-10, 10-20, 20-40 and 40-60 cm depths, and the nutrition, export and nutrient uptake, above ground biomass and grain yield of corn in 2008-2009 were evaluated after surface application of lime at rates of 0, 4, 8 and 12 t ha-1 in 2004, in a randomized complete block with three replications. Undisturbed soil columns were removed from plots that received lime rates, and another experiment was carried out on them, testing two hybrids, one aluminum-sensitive and another moderately sensitive to aluminum, and two moisture levels, simulating the presence and absence of water stress. Surface liming ameliorated soil acidity in all depths studied, and improved root environment throughout profile. Corn root growth was influenced by lime application, mainly at 0-10 cm depth. Liming had a positive effect on nutrition, export and nutrient uptake, resulting in a significant increase in corn grain yield. In the undisturbed columns, soil amendment by surface liming benefited root growth, nutrient uptake and dry matter production of corn plants, mainly in a water stress condition. In general, there was no difference in the response of both sensitive hybrid and moderately sensitive hybrid to aluminum toxicity with liming. It is concluded that the corn crop performance is ameliorated by the reduction in soil acidity through surface liming under no-till, but the corn crop development is little influenced by soil acidity when water availability is adequate. However, in a water stress condition, the soil acidity severely compromises the corn crop development under no-till system.
Keywords: Zea mays, L.; calcário dolomítico; absorção de nutrientes; cálcio; alumínio; acidez subsuperficial, déficit hídrico; Zea mays, L., dolomitic lime; nutrient uptake; calcium; aluminum; subsurface acidity; water deficit; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA